(untitled) (The Agriculturists, 2016)
An experiment on the efficacy of pheromone on capturing angoumois grain moth, Sitotroga cerealella (Olivier) was conducted in the laboratory of the Department of Entomology, Sher-e-Bangla Agricultural University, Bangladesh, using rice variety BR11. Pheromone (X-lure) trap was used as a treatment and data were recorded at different days and distances. The experiment was laid out in a Completely Randomized Design (CRD) with four replications. In case of total captured moth, the highest percentage (%) was recorded at 1st day (28.60%), whereas the lowest percentage (%) was recorded at 15th day (7.60%). It was also observed that with the increase of distance of pheromone trap, the % of captured moth was decreased. The pheromone X-lure was found useful only for monitoring S. cerealella (Olivier). The Agriculturists 2015; 13(2) 74-80